2017
DOI: 10.1155/2017/9498247
|View full text |Cite
|
Sign up to set email alerts
|

Autism-Like Behaviours and Memory Deficits Result from a Western Diet in Mice

Abstract: Nonalcoholic fatty liver disease, induced by a Western diet (WD), evokes central and peripheral inflammation that is accompanied by altered emotionality. These changes can be associated with abnormalities in social behaviour, hippocampus-dependent cognitive functions, and metabolism. Female C57BL/6J mice were fed with a regular chow or with a WD containing 0.2% of cholesterol and 21% of saturated fat for three weeks. WD-treated mice exhibited increased social avoidance, crawl-over and digging behaviours, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 81 publications
4
22
0
1
Order By: Relevance
“…These observations will be discussed, in turn, below. The present study on aged mice has, in general, replicated the principal findings reported for young mice fed the WD, such as impaired glucose tolerance, altered expression of Tlr4, Ppargc1a, and Ppargc1b (Strekalova et al, , 2016, and signs of emotional and cognitive abnormalities (Strekalova et al, , 2016Veniaminova et al, 2016Veniaminova et al, , 2017Veniaminova et al, , 2020. In comparison with young mice, aged animals exposed to WD gained weight and exhibited less profound changes in the expression of markers of inflammation and mitochondrial function.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These observations will be discussed, in turn, below. The present study on aged mice has, in general, replicated the principal findings reported for young mice fed the WD, such as impaired glucose tolerance, altered expression of Tlr4, Ppargc1a, and Ppargc1b (Strekalova et al, , 2016, and signs of emotional and cognitive abnormalities (Strekalova et al, , 2016Veniaminova et al, 2016Veniaminova et al, , 2017Veniaminova et al, , 2020. In comparison with young mice, aged animals exposed to WD gained weight and exhibited less profound changes in the expression of markers of inflammation and mitochondrial function.…”
Section: Discussionsupporting
confidence: 87%
“…Mice were fed with a standard laboratory diet (control diet, CD) with an energy content of 3.8 kcal/g, 4.3% of fat (1.3% of saturated fat) (D18071801, Research Diet Inc., New Brunswick, NJ, United States) or with a diet containing 0.2% of cholesterol, 21.3% of fat (10.5% of saturated fat), and an energy content of 4.6 kcal/g, Western diet (D11012302, Research Diet Inc., New Brunswick, NJ, United States) for 3 weeks as described elsewhere (Strekalova et al, , 2016Veniaminova et al, 2017). The content of the nutrients in calories and weight and the ingredients are indicated in Supplementary Table S1.…”
Section: Study Design and Dietsmentioning
confidence: 99%
See 3 more Smart Citations